2011
DOI: 10.1177/0194599811402172
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Transoral Robotic Surgery

Abstract: Objective To report long-term, health-related quality of life (HRQOL) outcomes in patients treated with transoral robotic surgery (TORS). Study Design Prospective clinical study on functional and HRQOL outcomes in TORS. Setting University tertiary care facility. Subjects Patients who underwent TORS at The Ohio State University Medical Center. Methods All patients undergoing TORS were asked to complete the Head and Neck Cancer Inventory before treatment, and at 3 weeks, 3, 6, and 12 months postoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(22 citation statements)
references
References 29 publications
2
19
1
Order By: Relevance
“…A single study of radical tonsillectomy reported the placement of gastrostomy tubes intraoperatively in all patients. 15 PEG placement did not differ significantly when stratified by AJCC stage, 12 but one series reported PEG placement exclusively in patients with T3 or T4 tumors and mostly in patients with tongue base primaries. 11 Chronic gastrostomy dependence was reported in 11 of 12 studies, and ranged from 0% to 7% (mean follow-up: 11–32 months), regardless of disease stage.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…A single study of radical tonsillectomy reported the placement of gastrostomy tubes intraoperatively in all patients. 15 PEG placement did not differ significantly when stratified by AJCC stage, 12 but one series reported PEG placement exclusively in patients with T3 or T4 tumors and mostly in patients with tongue base primaries. 11 Chronic gastrostomy dependence was reported in 11 of 12 studies, and ranged from 0% to 7% (mean follow-up: 11–32 months), regardless of disease stage.…”
Section: Resultsmentioning
confidence: 91%
“…Time to oral intake varied by T-stage (Table 2). Oral intake was earlier among 3 series that excluded T4 tumors; 12,13 96% of patients began oral intake on POD #1 after TORS for T1–T2 tumors 12 and mean time to oral intake was 2 days after TORS for T1–T3 OPC tumors. 13 In contrast, only 51% of patients began oral intake on POD #1 after TORS when data were reported for patients of all T-stages (T1–T4).…”
Section: Resultsmentioning
confidence: 96%
“…Not all the patients are good candidates for TORS because some of them may present some limiting factors, mostly affecting proper surgical exposure, such as trismus, narrow arched mandible, full dentition, and retrognathia [42]. Access to the tumour may also be influenced by the site and the extension of the tumour, and the equipment employable by the surgeon [16].…”
Section: Discussionmentioning
confidence: 99%
“…However, the benefits of decreased operative time and decreased length of hospital stay could offset this cost [45]. Operating room setup time and surgical time can be significantly long at the beginning, but all published articles demonstrated a precipitously and significant reduction of those times as the surgeons gained experience with the Da Vinci Surgical System [42] (Table 3). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation